Vertical variations of soil carbon under different land uses in a karst critical zone observatory (CZO), SW China - Qin, Caiqing; Li, Si-Liang; Yu, Guang-Hui; Bass, Adrian M.; Yue, Fu-Jun; Xu, Sheng (Geoderma, 2022)
[Display omitted] •There is an active SIC-CO2-SOC system and a fast C cycle in karst soils.•The impact of biological factors on SIC in karst soils exceeds expectations.•Both SOC and SIC are labile and susceptible to land use change in karst regions.•Ceasing tillage benefits SOC restoration which mainly occurs within topsoil. Soil is a key carbon reservoir balancing global carbon budget and regulating climate change. Barren soils in karst zones have weak capacity for soil and water conservation and are readily erodible, making the carbon biogeochemical processes within karst soils potentially rapid and complex. To explore the vertical variation of soil carbon under karst conditions and its response to land-use change, this study investigated concentrations and isotopic compositions of both soil organic and inorganic carbon (SOC and SIC) in different depths of four land-use types in a typical karst region, SW China. Results show that as soil depth increases, SOC concentrations decrease, and its δ13C ratios (from −27.3‰ to −19.4‰) increase in 0–20 cm depth but decrease at depths below 20 cm. The fresh SOC is mostly sequestered and cycled within the topsoil and subject to different controls than that of the subsoil. The turnover rate of SOC in karst soils does not directly co-vary with isotopic fractionation among different land uses. Long-term cultivation causes SOC loss from karst soils, which can be alleviated or even partially restored after farming cessation. By contrast, SIC represents < 10% of soil total carbon. The vertical heterogeneity of SIC variation and the direct influence of biological factors on SIC are both weaker relative to SOC. The low δ13C ratios of SIC (from −20.4‰ to −3.0‰) indicate there is intense dissolution and reprecipitation of pedogenic carbonate within karst soil, especially in the upper cultivated layers. These results highlight that both SOC and SIC are labile and susceptible to land-use change in karst zones, which need to be considered in estimating karst carbon sink and its role in balancing global carbon budget on variable temporal scales.